Preparation method and application of nitrogen-doped carbon-based bifunctional material

CN121402044BActive Publication Date: 2026-10-27ZHEJIANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511990869.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-26
Publication Date
2026-10-27
Estimated Expiration
2045-12-26

AI Technical Summary

Technical Problem

但生物炭基DFM反应温度相对较高,在实际应用中面临能耗限制的挑战

Benefits of technology

相对于现有技术,本发明具有以下有益效果:本发明提供了基于氮掺杂生物炭载体的新型双功能材料具有优异的低温ICCM性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121402044B_ABST
    Figure CN121402044B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of a nitrogen-doped carbon-based bifunctional material, and relates to the following steps: high-temperature carbonization of guanine under a nitrogen atmosphere, washing, suction filtration and drying of the guanine after cooling to room temperature to obtain biochar; adding Ni(NO3)2.6H2O and Mg(NO3)2.6H2O with a molar ratio of 1:1 into deionized water to uniformly stir the deionized water and obtain a solution; adding the biochar into the solution to stir, so that the mass ratio of nickel-magnesium metal to the biochar is 1:(0.3-1.5); transferring the mixed solution into an oil bath pot to stir and dry until water is completely evaporated; transferring the solid substance into a crucible to roast under the protection of a nitrogen atmosphere, and obtaining the nitrogen-doped carbon-based bifunctional material after cooling. The one-pot preparation process is simple, environment-friendly, and the prepared nitrogen-doped carbon-based bifunctional material is low in cost, and can realize high-performance CO2 capture and in-situ methanation of flue gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of integrated flue gas carbon capture and in-situ methanation technology, specifically relating to a method for preparing and applying a nitrogen-doped carbon-based bifunctional material. Background Technology

[0002] Traditional carbon capture technologies are typically separated from storage (CCS) or utilization (CCU) processes, resulting in core bottlenecks such as high energy consumption, complex processes, and poor economic efficiency. In recent years, integrated carbon capture and in-situ conversion (ICCC) technology has emerged as a promising alternative. This technology couples CO2 adsorption and catalytic hydrogenation processes within the same reactor, utilizing bifunctional materials (DFM) to first capture CO2, and then converting it in-situ into high-value-added fuels or chemicals under hydrogenation conditions. This approach promises to significantly reduce system complexity and energy consumption, achieving closed-loop resource utilization of CO2. Among various conversion pathways, the catalytic hydrogenation of CO2 to methane (Sabatier reaction) is considered a realistic and efficient route because its products can be directly incorporated into existing natural gas networks. The design of high-performance DFMs typically requires integrating two functional sites: highly efficient CO2 adsorption sites (such as alkaline metal oxides like MgO and CaO) and excellent hydrogenation activity sites (such as metals like Ni and Ru). Ni / MgO-based DFMs have great potential in ICCM applications because the catalytic component Ni has relatively high activity and low cost, and the adsorption temperature of the adsorbent component MgO is also consistent with the methanation reaction temperature (200-500℃).

[0003] Support materials can significantly improve the dispersion and activity of active sites in DFM and are widely used in ICCM. Currently, most research on supports in this field focuses on traditional metal oxides. Notably, our previous exploratory work showed that using widely available and inexpensive biomass-derived carbon as a DFM support is feasible. However, biochar-based DFM reaction temperatures are relatively high, posing a challenge of energy consumption limitations in practical applications. This discovery prompted us to seek further innovative breakthroughs. Zhou et al. prepared a three-dimensional honeycomb nitrogen-doped carbon (NC) supported core-shell structure NiO@Ni nanoparticles (NiO@Ni / NC-500) catalyst. This material achieved a CO2 methanation rate of 3.7 mmol / (g·h) at 200 °C. The study indicated that the high specific surface area and three-dimensional conductive network of nitrogen-doped carbon promoted reactant diffusion and electron transfer. Furthermore, the synergistic effect of pyridine nitrogen and graphitic nitrogen enhanced the metal-support electronic interaction, optimized the adsorption energy of Ni active sites, and thus significantly improved methane selectivity and stability. Martin Muhler et al. prepared a high-performance Ni / NCNT catalyst for CO2 methanation using nitrogen-doped carbon nanotubes (NCNTs) as a support. The catalyst achieved a CO2 conversion exceeding 50% and a CH4 selectivity of up to 95% at 340℃ and 1 bar. Mechanistic studies showed that the nitrogen functional groups in the nitrogen-doped carbon nanotubes effectively anchored nickel nanoparticles, preventing sintering, while simultaneously enhancing CO2 adsorption capacity, thus improving the catalyst's activity and stability. Based on research into the structure-activity relationship of biochar supports, we realized that nitrogen doping of biochar can simultaneously enhance CO2 adsorption and metal dispersion, potentially leading to a significant reduction in reaction temperature. This innovative choice of support not only maintains the economic advantages of biochar but also holds promise for a major breakthrough in low-temperature activity. Therefore, exploring the application of bifunctional materials based on nitrogen-doped carbon supports in the field of ICCM is essential. Summary of the Invention

[0004] To address at least one of the aforementioned problems, this invention provides a method for preparing nitrogen-doped carbon-based bifunctional materials and their applications.

[0005] To achieve the above objectives, the present invention employs the following technical means: The first aspect of this invention provides a method for preparing nitrogen-doped carbon-based bifunctional materials, the method being as follows: Guanine was carbonized at high temperature under a nitrogen atmosphere, cooled to room temperature, washed with deionized water, filtered, and dried to obtain biochar. Ni(NO3)2·6H2O and Mg(NO3)2·6H2O in a molar ratio of 1:1 were added to deionized water and stirred until homogeneous to obtain a solution. Biochar was added to the solution and stirred to make the mass ratio of nickel and magnesium metal to biochar 1:(0.3-1.5). The mixed solution was transferred to an oil bath and dried while stirring until the water was completely evaporated. The solid material was transferred to a crucible and calcined under a nitrogen atmosphere. After cooling, nitrogen-doped carbon-based bifunctional material was obtained.

[0006] In some embodiments of the present invention, preferably, the sum of the masses of nickel and magnesium metals to the mass ratio of biochar is 1:0.7.

[0007] In some embodiments of the present invention, the high-temperature carbonization temperature is 1000-1200°C.

[0008] In some embodiments of the present invention, the high-temperature carbonization heating rate is 8-10℃ / min, and is maintained for 0.8-1.2h.

[0009] In some embodiments of the present invention, the nitrogen atmosphere conditions during the high-temperature carbonization process are 80-100 mL / min.

[0010] In some embodiments of the present invention, the calcination conditions are: calcination temperature 550℃-650℃, heating rate 4-5℃ / min, and calcination time 1.5-2.5 h.

[0011] In some embodiments of the present invention, the nitrogen atmosphere condition during the calcination of the solid material is 80-100 mL / min.

[0012] The second aspect of the present invention provides nitrogen-doped carbon-based bifunctional materials prepared by the method described in the first aspect.

[0013] The third aspect of this invention provides the application of the nitrogen-doped carbon-based bifunctional materials described in the second aspect in integrated flue gas carbon capture and in-situ methanation.

[0014] In some embodiments of the present invention, the application temperature is 250-300°C.

[0015] In some embodiments of the present invention, the nitrogen-doped carbon-based bifunctional material is pre-reduced in a 40% H2 atmosphere at 450-500°C before application.

[0016] Beneficial effects of the present invention Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a novel bifunctional material based on nitrogen-doped biochar support with excellent low-temperature ICCM performance.

[0017] The one-pot preparation process employed in this invention is simple and environmentally friendly, and the resulting nitrogen-doped carbon-based bifunctional material is inexpensive, enabling high-performance CO2 capture and in-situ methanation of flue gas. The results of the examples demonstrate that the nitrogen-doped carbon-based bifunctional material prepared by this invention exhibits excellent ICCM performance at low temperatures of 250℃-300℃, significantly outperforming DFM with pure biochar as the support. Attached Figure Description

[0018] Figure 1 The SEM image of Ni-MgO@0.7NC prepared in Example 3 of the present invention is shown; Figure 2 SEM images of the bifunctional materials prepared in Examples 1 and 5 of the present invention are shown; wherein, (a) is Example 1 and (b) is Example 5; Figure 3 The images show low-magnification and high-magnification TEM images of the bifunctional material prepared in Example 3 of the present invention; wherein, (a) is a low-magnification TEM image and (b) is a high-magnification TEM image. Figure 4 The EDX mapping image of Ni-MgO@0.7NC prepared in Example 3 of the present invention is shown; Figure 5 The pore size distribution characteristics of the bifunctional materials prepared in Examples 1, 3, 5 and Comparative Example 2 of the present invention are shown. Figure 6 The pore size distribution characteristics of the bifunctional materials prepared in Examples 1, 3, 5 and Comparative Example 2 of the present invention are shown. Figure 7 The pore structure parameters of the bifunctional materials prepared in Examples 1, 3, 5 and Comparative Example 2 of the present invention are shown. Figure 8 The comparison of CO2 capture and methanation performance of the bifunctional materials prepared in Example 1 and Comparative Example 1 of the present invention at 300°C is shown. Figure 9 The CO2 capture and methanation performance of the DFM prepared in Example 3 and Comparative Example 2 of the present invention at 250°C and 300°C are shown. Figure 10 The CO2 capture and methanation properties of the bifunctional materials prepared in Examples 1-5 of this invention are shown. Detailed Implementation

[0019] The following examples are used to illustrate preferred embodiments of the invention. Those skilled in the art will understand that the techniques disclosed in the examples represent techniques discovered by the inventors that can be used to implement the invention, and therefore can be considered preferred embodiments for implementing the invention. However, those skilled in the art should understand from this specification that many modifications can be made to the specific embodiments disclosed herein, still yielding the same or similar results, without departing from the spirit or scope of the invention.

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains, and all materials disclosed herein and cited therein are incorporated herein by reference. Many equivalent techniques of specific embodiments of the invention described herein will be recognized or can be understood by ordinary experimentation by those skilled in the art. These equivalents will be included in the claims.

[0021] The technical solution of this application will be further described in detail below with reference to specific embodiments.

[0022] Example 1 First, 10g of guanine was weighed into a crucible. Then, the crucible was carbonized at 1000℃ in a muffle furnace under a nitrogen atmosphere (100mL / min) at a heating rate of 10℃ / min for 1 hour. After cooling to room temperature, the carbonized black substance was removed and washed in deionized water with stirring for 12 hours. Subsequently, after washing with deionized water, filtration, and drying, nitrogen-doped carbon was obtained, named NC.

[0023] Then, 3.78 g of Ni(NO3)2·6H2O and 3.20 g of Mg(NO3)2·6H2O were added to 200 mL of deionized water and stirred for 20 min. Subsequently, 0.3 g of nitrogen-doped carbon was weighed and added to the above solution, and stirring continued for 30 min. The mixed solution was then transferred to an oil bath at 90 °C and dried while stirring until all moisture was evaporated. Finally, the resulting solid was transferred to a crucible and calcined at 600 °C for 2 h in a muffle furnace under a nitrogen atmosphere (nitrogen flow rate 100 mL / min, heating rate 5 °C / min). After the muffle furnace temperature cooled to room temperature, Ni-MgO@0.3NC was obtained.

[0024] Example 2 First, 10g of guanine was weighed into a crucible. Then, the crucible was carbonized at 1000℃ in a muffle furnace under a nitrogen atmosphere (100mL / min) at a heating rate of 10℃ / min for 1 hour. After cooling to room temperature, the carbonized black substance was removed and washed in deionized water with stirring for 12 hours. Subsequently, after washing with deionized water, filtration, and drying, nitrogen-doped carbon was obtained, named NC.

[0025] Then, 3.78 g of Ni(NO3)2·6H2O and 3.20 g of Mg(NO3)2·6H2O were added to 200 mL of deionized water and stirred for 20 min. Next, 0.5 g of nitrogen-doped carbon was weighed and added to the solution, and stirring continued for 30 min. The mixture was then transferred to an oil bath at 90 °C and dried while stirring until all moisture was evaporated. Finally, the resulting solid was transferred to a crucible and calcined at 600 °C for 2 h in a muffle furnace under nitrogen atmosphere (nitrogen flow rate 100 mL / min, heating rate 5 °C / min). After the muffle furnace temperature cooled to room temperature, Ni-MgO@0.5NC was obtained.

[0026] Example 3 First, 10g of guanine was weighed into a crucible. Then, the crucible was carbonized at 1000℃ in a muffle furnace under a nitrogen atmosphere (100mL / min) at a heating rate of 10℃ / min for 1 hour. After cooling to room temperature, the carbonized black substance was removed and washed in deionized water with stirring for 12 hours. Subsequently, after washing with deionized water, filtration, and drying, nitrogen-doped carbon was obtained, named NC.

[0027] Then, 3.78 g of Ni(NO3)2·6H2O and 3.20 g of Mg(NO3)2·6H2O were added to 200 mL of deionized water and stirred for 20 min. Subsequently, 0.7 g of nitrogen-doped carbon was weighed and added to the above solution, and stirring continued for 30 min. The mixed solution was then transferred to an oil bath at 90 °C and dried while stirring until all moisture was evaporated. Finally, the resulting solid was transferred to a crucible and calcined at 600 °C for 2 h in a muffle furnace under a nitrogen atmosphere (nitrogen flow rate 100 mL / min, heating rate 5 °C / min). After the muffle furnace temperature cooled to room temperature, Ni-MgO@0.7NC was obtained.

[0028] Example 4 First, 10g of guanine was weighed into a crucible. Then, the crucible was carbonized at 1000℃ in a muffle furnace under a nitrogen atmosphere (100mL / min) at a heating rate of 10℃ / min for 1 hour. After cooling to room temperature, the carbonized black substance was removed and washed in deionized water with stirring for 12 hours. Subsequently, after washing with deionized water, filtration, and drying, nitrogen-doped carbon was obtained, named NC.

[0029] Then, 3.78 g of Ni(NO3)2·6H2O and 3.20 g of Mg(NO3)2·6H2O were added to 200 mL of deionized water and stirred for 20 min. Next, 1 g of nitrogen-doped carbon was weighed and added to the solution, and stirring continued for 30 min. The mixture was then transferred to an oil bath at 90 °C and dried while stirring until all moisture was evaporated. Finally, the resulting solid was transferred to a crucible and calcined at 600 °C for 2 h in a muffle furnace under nitrogen atmosphere (nitrogen flow rate 100 mL / min, heating rate 5 °C / min). After the muffle furnace temperature cooled to room temperature, Ni-MgO@1NC was obtained.

[0030] Example 5 First, 10g of guanine was weighed into a crucible. Then, the crucible was carbonized at 1000℃ in a muffle furnace under a nitrogen atmosphere (100mL / min) at a heating rate of 10℃ / min for 1 hour. After cooling to room temperature, the carbonized black substance was removed and washed in deionized water with stirring for 12 hours. Subsequently, after washing with deionized water, filtration, and drying, nitrogen-doped carbon was obtained, named NC.

[0031] Then, 3.78 g of Ni(NO3)2·6H2O and 3.20 g of Mg(NO3)2·6H2O were added to 200 mL of deionized water and stirred for 20 min. Subsequently, 1.5 g of nitrogen-doped carbon was weighed and added to the above solution, and stirring continued for 30 min. The mixed solution was then transferred to an oil bath at 90 °C and dried while stirring until all moisture was evaporated. Finally, the resulting solid was transferred to a crucible and calcined at 600 °C for 2 h in a muffle furnace under a nitrogen atmosphere (nitrogen flow rate 100 mL / min, heating rate 5 °C / min). After the muffle furnace temperature cooled to room temperature, Ni-MgO@1.5NC was obtained.

[0032] Comparative Example 1 First, weigh 10g of corn cob powder into a crucible. Then, place the crucible in a muffle furnace under a nitrogen atmosphere (100 mL / min) at 1200℃ for the first carbonization, with a heating rate of 10℃ / min, and hold for 1h. After the temperature drops to room temperature, remove the carbonized black material and wash it in a 0.5 mol / L sulfuric acid solution with stirring for 12h. Subsequently, wash with deionized water, filter, and dry to obtain primary carbonized biochar. Then, place the primary carbonized biochar in the crucible again and perform a second carbonization in a muffle furnace under a nitrogen atmosphere at 600℃, with a heating rate of 5℃ / min, and hold for 2h. Finally, biochar with strong thermal stability is obtained.

[0033] Subsequently, 3.78 g of Ni(NO3)2·6H2O and 3.20 g of Mg(NO3)2·6H2O were added to deionized water and stirred for 20 min. Then, 1 g of the prepared biochar was weighed and added to the above solution, and stirring was continued for 30 min. The mixed solution was then transferred to an oil bath at 90°C and dried while stirring until all moisture was evaporated. Finally, the resulting solid was transferred to a crucible and calcined at 600°C for 2 h in a muffle furnace under nitrogen atmosphere (nitrogen flow rate 100 mL / min, heating rate 5°C / min). After the muffle furnace temperature cooled to room temperature, Ni-MgO@C was obtained.

[0034] Comparative Example 2 First, 10g of glucose was weighed into a crucible. Then, the crucible was carbonized at 1000℃ in a muffle furnace under a nitrogen atmosphere (100mL / min) at a heating rate of 10℃ / min for 1 hour. After cooling to room temperature, the carbonized black substance was removed and washed in deionized water with stirring for 12 hours. Subsequently, after washing with deionized water, filtration, and drying, biochar was obtained and named C.

[0035] Then, 3.78 g of Ni(NO3)2·6H2O and 3.20 g of Mg(NO3)2·6H2O were added to 200 mL of deionized water and stirred for 20 min. Next, 0.7 g of biochar was weighed and added to the solution, and stirring continued for 30 min. The mixture was then transferred to an oil bath at 90 °C and dried while stirring until all moisture was evaporated. Finally, the resulting solid was transferred to a crucible and calcined at 600 °C for 2 h in a muffle furnace under nitrogen atmosphere (nitrogen flow rate 100 mL / min, heating rate 5 °C / min). After the muffle furnace temperature cooled to room temperature, Ni-MgO@0.7C was obtained.

[0036] Performance testing and characterization (1) The SEM test results of the bifunctional materials prepared in Examples 1, 3, and 5 are as follows: Figure 1 and Figure 2 As shown.

[0037] The results showed that the Ni-MgO@0.7NC prepared in Example 3 exhibited a distinct fibrous interwoven network structure with densely packed nanoparticles attached to the surface. These particles clearly serve as the supported adsorption and catalytic sites. In Ni-MgO@0.3NC with even lower NC content, these particles even coalesced into irregular sheet-like aggregates, while the fibrous carbon support structure was significantly reduced. Figure 2a. The morphology of Ni-MgO@1.5NC is basically the same as that of Ni-MgO@0.7NC, but the nanoparticles on the surface of Ni-MgO@1.5NC are smaller. The above phenomena indicate that the higher the NC carrier content, the smaller the particle size and the better the dispersibility of the two active sites.

[0038] (2) TEM testing and analysis were performed on the bifunctional material prepared in Example 3. Figure 3 and Figure 4 As shown.

[0039] Figure 3 Image a shows a low-magnification TEM image of Ni-MgO@0.7NC prepared in Example 3. As can be seen from the image, the sample mainly consists of well-dispersed spherical nanoparticles dispersed on carbon nanosheets, and the size distribution of the nanoparticles is relatively uniform. Clearly, the nanoparticles distributed on the carbon nanosheets represent the two active sites, which further demonstrates the good dispersibility of these two sites.

[0040] Figure 3 b presents a high-resolution TEM image of Ni-MgO@0.7NC. The clear lattice fringes indicate excellent crystallinity of the material. The measured interplanar spacings in the image are 0.21 and 0.35 nm, corresponding to Mg... 0.4 Ni 0.6 The O (200) crystal plane and the (002) crystal plane of nitrogen-doped carbon.

[0041] Depend on Figure 4 The EDX mapping of Ni-MgO@0.7NC shows that the signals of C and N are consistently distributed throughout the material, while the distributions of O, Mg, and Ni largely overlap. This further indicates that the two active sites form a solid solution of Mg. 0.4 Ni 0.6 O.

[0042] (3) The pore structure of the bifunctional materials prepared in Examples 1, 3, 5 and Comparative Example 2 was characterized as follows: Figures 5 to 7 .

[0043] The results show that: Figure 5 As can be seen, all samples exhibited type IV isotherms, indicating that they possess well-developed mesoporous structures. Among them, the N2 adsorption capacity of Ni-MgO@1.5NC was significantly higher than that of other samples, suggesting that it has a larger specific surface area.

[0044] Figure 6The NLDFT pore size distribution results show that the pore size of all DFMs is mainly concentrated in the range of 10-35 nm, with a small number of micropores present, exhibiting a hierarchical pore structure. Among them, Ni-MgO@0.7C has the highest proportion of micropores, and the number of micropores gradually decreases with the increase of the support content. In Ni-MgO@0.3NC with the lowest NC content, there are almost no micropores.

[0045] A detailed comparison of the pore structure parameters of several DFMs can be found in Figure 7 With the increase of biochar carrier content, the specific surface area and total pore volume of the material gradually increased, among which Ni-MgO@1.5NC had the highest specific surface area (141 m²). 2 / g), far exceeding Ni-MgO@0.3NC (69 m 2 / g).

[0046] (4) The CO2 adsorption and methanation performance of the bifunctional materials prepared in Examples 1-5 and Comparative Examples 1-2 under different working conditions were tested by fixed-bed adsorption breakthrough experiments.

[0047] All materials must undergo pre-reduction treatment at 500℃ in a 40% H2 atmosphere before ICCM performance testing. The specific test procedure is as follows: First, approximately 200 mg of DFM is weighed and loaded into a fixed-bed reactor. The temperature is raised to 500℃ at a rate of 10℃ / min using pure N2 (space velocity 30000 mL / h / g). Then, the gas is replaced with an equal flow rate of 40% H2 mixture for DFM reduction. After reduction, the reactor is purged with pure N2 for 20 minutes until the outlet hydrogen concentration drops to zero. Next, the reactor temperature is adjusted to the target test temperature (250℃ or 300℃) to begin ICCM testing. ICCM testing begins with a 20-minute CO2 capture using a 100 mL / min 10% CO2 mixture. Then, the gas is switched to an equal flow rate of 10% H2 mixture for a 20-minute in-situ CO2 methanation reaction. After the reaction, the reactor is purged with pure N2 for 20 minutes. The above experiments yield curves showing the changes in the concentrations of gases such as CO2, CO, H2, and CH4 over time. The following formulas can be used to calculate the CO2 adsorption / desorption rate and conversion, CO production, CH4 production, and selectivity.

[0048]

[0049]

[0050]

[0051]

[0052] Here q adCO2 (mmol / g) represents the adsorption capacity, Q represents the total gas flow rate (mL / min), and C represents the total gas flow rate. in (mg / m 3 ) and C out q represents the CO2 inlet and outlet mass concentrations, respectively, and m represents the DFM mass. X (mmol / g) represents the amount produced, C X (mg / m 3 ) represents the mass concentration, where X is one of CO, CH4, and desorbed CO2. Mr is the relative molecular mass of the corresponding molecule. η is the CO2 conversion rate, X CH4 CH4 selectivity.

[0053] Figure 8 The CO2 capture and methanation performance of the bifunctional materials prepared in Example 3 and Comparative Example 1 at 300°C is shown.

[0054] Although Comparative Example 1 exhibited excellent ICCM performance at 400°C, its ICCM performance significantly decreased at a relatively lower temperature (300°C). From Figure 3 It is evident that the Ni-MgO@0.7NC material prepared by this invention, using nitrogen-doped carbon as a support, exhibits significantly superior overall performance compared to Ni-MgO@C, which uses corn cob-derived traditional biochar as a support. Specifically, Ni-MgO@0.7NC demonstrates a CO2 adsorption capacity approximately 2.1 times that of Ni-MgO@C, a CO2 conversion rate 3.8 times higher, and a methane selectivity exceeding 99%, while significantly suppressing the formation of the byproduct CO. This fully demonstrates that the nitrogen doping strategy enhances CO2 adsorption by introducing basic sites and optimizes the electronic structure of the nickel-magnesium active centers, thereby synergistically strengthening the material's carbon capture and in-situ methanation capabilities, and significantly improving the material's low-temperature performance.

[0055] Figure 9 The CO2 capture and methanation performance of DFM prepared in Example 3 and Comparative Example 2 at different reaction temperatures are shown.

[0056] Depend on Figure 9It is evident that, when the biochar support content is the same, NC as a support significantly enhances the overall ICCM performance of the material regardless of the temperature: at 300°C, the CO2 adsorption capacity of Ni-MgO@0.7NC (1.46 mmol / g) far exceeds that of Ni-MgO@0.7C (0.97 mmol / g), which is attributed to the enhanced interaction with CO2 by the basic sites introduced by nitrogen doping. More importantly, its CO2 conversion rate (81.62% vs. 49.87%) and CH4 yield (1.18 mmol / g vs. 0.46 mmol / g) achieved a leapfrog improvement, while the CH4 selectivity remained at an extremely high level of over 99% (compared to 95.30%), and the CO byproduct yield was further suppressed. This fully demonstrates that nitrogen doping not only enhances the adsorption capacity but also greatly strengthens the hydrogenation activity of the catalytic sites and the selectivity for the CH4 pathway by optimizing the electronic structure of metallic nickel (Ni) and improving its dispersion and stability.

[0057] Figure 10 The CO2 capture and methanation performance of the bifunctional materials prepared in Examples 1-5 at 300°C is shown.

[0058] Depend on Figure 10 It is evident that the DFM with an NC addition of 0.7 exhibits the best performance, indicating that this ratio achieves the optimal structure-property relationship of the material structure. It provides sufficient basic sites for CO2 adsorption while ensuring adequate exposure of Ni active sites, thus realizing an ideal integration of adsorption and catalytic functions. Too low a support ratio (0.3NC, 0.5NC) leads to poor dispersion of adsorption-catalytic active sites, preventing them from fully functioning. Conversely, too high a support ratio (1.0NC, 1.5NC) results in excessive separation of adsorption-catalytic active sites, increasing mass transfer resistance and hindering subsequent hydrogenation conversion of captured CO2. Overall, all five bifunctional materials exhibit excellent low-temperature ICCM performance, with the material with an NC addition of 0.7 showing the best performance.

[0059] All documents mentioned in this invention are incorporated herein by reference as if each document were individually incorporated by reference. Furthermore, it should be understood that after reading the foregoing teachings of this invention, those skilled in the art can make various alterations or modifications to this invention, and these equivalent forms also fall within the scope defined by this application.

Claims

1. A method for preparing a nitrogen-doped carbon-based bifunctional material, characterized in that, The method is as follows: Guanine was carbonized at high temperature under a nitrogen atmosphere, cooled to room temperature, washed with deionized water, filtered, and dried to obtain biochar. Ni(NO3)2·6H2O and Mg(NO3)2·6H2O in a molar ratio of 1:1 were added to deionized water and stirred until homogeneous to obtain a solution. Biochar was added to the solution and stirred to make the mass ratio of nickel and magnesium metal to biochar 1:(0.3-1.5). The mixed solution was transferred to an oil bath and dried while stirring until the water was completely evaporated. The solid material was transferred to a crucible and calcined under a nitrogen atmosphere. After cooling, nitrogen-doped carbon-based bifunctional material was obtained. The high-temperature carbonization temperature is 1000-1200℃; the heating rate is 8-10℃ / min, and the temperature is maintained for 0.8-1.2h. During the high-temperature carbonization process, the nitrogen atmosphere condition is 80-100 mL / min; The calcination conditions are as follows: calcination temperature 550℃-650℃, heating rate 4-5℃ / min, calcination time 1.5-2.5 h; during the calcination process, the nitrogen atmosphere condition is 80-100 mL / min.

2. The nitrogen-doped carbon-based bifunctional material prepared by the method of claim 1.

3. The application of the nitrogen-doped carbon-based bifunctional material according to claim 2 in integrated flue gas carbon capture and in-situ methanation.

4. The application according to claim 3, characterized in that: The application temperature is 250-300℃.

5. The application according to claim 3, characterized in that: The nitrogen-doped carbon-based bifunctional material is pre-reduced in a 40% H2 atmosphere at 450-500℃ before application.

Citation Information

Patent Citations

  • Click chemistry on heterogeneous catalysts

    EP2239053A1

  • System and method for synthesis of molecular imaging probes including fdg

    WO2004093652A2